Tantangan Miskonsepsi dan Pengaruh Literasi Sains dalam Proses Pembelajaran IPA di Sekolah Dasar - Kasanah, Uswantun; Sanjaya, Fifi; Indahwati, Christine; Wimbawati, PK Ary; Yasa, I Wayan Dresti; Suma, Ketut; Suastra, Wayan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Quantitative descriptive research with literature credibility and data source substitution was conducted on the independent variable of science literacy in the IPA learning process in elementary schools in its influence on overcoming student misconceptions as the dependent variable. The study aimed to determine the relationship between the independent and dependent variables, the significance of the relationship between the research variables, and to determine whether or not there was an influence of the variables. The population of elementary school science teachers with third, fourth, and fifth-grade students as respondents in questionnaires, interviews, and observation participants resulted in a significant negative correlation between the variables and a determination coefficient of variable X on variable Y.